Corpus Linguistics on the Impression Management Strategy of Indonesian Public Officials after Covid-19 Denial Statements - Miftha, Pratiwi; Rindang Senja, Andarini; Rini, Setiyowati; Anang Dwi, Santoso (KOME, 2023)
With the Covid-19 pandemic, public officials in Indonesia were prone to making inaccurate claims and to enacting policies that the public might have overlooked due to a lack of understanding of complex situations. However, after making these mistakes, public officials needed to restore their reputation and create a positive impression. This study aimed to investigate the impression management strategies employed by Indonesian public officials following such incidents. The researchers analysed a dataset of 2,000 Instagram captions from seven public officials over the course of a year, totalling 13,725 words and 196,154 tokens, using corpus linguistic techniques such as frequent words and keyword lists. The findings revealed that officials used different strategies such as ingratiation, self-promotion and supplication to manage their impression, and that positive attitudes and hard work were the main tools used by officials to improve their public image.